Performance investigation of a rectangular spiral flow PV/T collector with a novel form-stable composite material. (5th January 2021) - Das, Dudul; Bordoloi, Urbashi; Kamble, Akash Dilip; Muigai, Harrison Hihu; Pai, Ranjith Krishna; Kalita, Pankaj
Highlights: Development of rectangular spiral absorber based transparent PV/T. PCM-water hyacinth biochar based form stable thermal energy storage material. 17 times enhancement in thermal conductivity of the composite as that of pure PCM. Application of the composite limited the PV temperature within 30 °C. 18.4% improvement in electrical output as compared to PV. Abstract: The electrical output of the Photovoltaic (PV) cells decreases with the increase in the operating temperature. To address the issue of electrical power drop in PV, a new hybrid collector called photovoltaic-thermal (PV/T) module has been proposed by the researchers. PV/T combines a PV and thermal absorber; it helps in cooling of PV and to harness the waste heat from PV for utilizing in low-temperature applications. However, the cooling uniformity and thermal efficiency remain to be major challenges for the broader applicability of PV/T. In this work, a novel rectangular spiral tube only absorber is developed with a transparent multi-crystalline PV module with absorber tubes directly glued to the PV backside. A novel form-stable composite developed by simple impregnation method using PCM (OM35) and biochar derived from water hyacinth. This novel composite is embedded in the enclosure formed by the PV and back cover to improve cooling uniformity and better absorption of incoming radiation due to the blackish appearance of the composite. In the composite, 5% by wt aluminium metal powder is added. The thermal conductivity of the composite is found to improve by 1.66 times than that of pure PCM, while aluminium metal powder is added. The heat of fusion is calculated to be 78 J/g. The developed PV/T system has been experimentally evaluated under outdoor conditions. The average electrical, thermal, energy and exergy efficiency of the PV/T system with novel form-stable thermal energy storage material is reported to be 13 ± 5.04%, 66.6 ± 5.48%, 79.6 ± 5.53%, and 15 ± 5.58% respectively, whereas the average electrical efficiency PV during the experiment found to be 10.7 ± 5.04%. The electrical efficiency of the PV module used is 14.64% under Standard Test Conditions. There is an improvement of 18.4% in electrical output as compared to PV with this novel arrangement.